Strategi Penataan Ruang Publik Pada Kota Lama Di Semarang Berdasarkan Public Space Index Pada Masa Pandemi COVID-19 - Helga Ezra Novita Panjaitan; Grandy Loranessa Wungo (Jurusan Perencanaan Wilayah dan Kota, 2022)
Urban spatial planning cannot be separated from the element of public open space. During the COVID-19 pandemic, public space are also used as alternative tourism munity as well as a place to unwind, so that must be balanced with good quality as well. In this study, researchers took the road corridor Letjen Soeprapto which is one of the public spaces in the Kota Lama which has quite a number of building arrangements including high priority buildings, however durig the COVID-19 pandemic this route still uses normal standards before the pandemic and did not have a design that was responsive to the pandemic so that it experionced a drastic decrease in visitors. The purpose of this study is to develop a strategy for structuring the public space of Kota Lama based on the Public Space Index during the COVID-19 pandemic. The quality measurement is based on the Public Space Index (PSI) which is based on the observations of researchers and perceptions of visitors. The analysis used is Behavior Mapping, Simpson's Diversity Index, Public Space Index, and SWOT analysis. The results of the Public Space Index as a whole, the quality of public space in the Old City is quite good with a total value of 108.39 PSI from a maximum value of 150, so that the structuring strategy obtained from the SWOT analysis shows that in general the arrangement that can be done is the addition of responsive facilities during the COVID- 19 pandemic.